2023
DOI: 10.1007/s10238-023-01025-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum CA724 has no diagnostic value for gastrointestinal tumors

Abstract: Objective This study aimed to explore the predictive values of serum carcinoembryonic antigen (CEA), carbohydrate antigen (CA) 199, CA125 and CA724 in the diagnosis of gastrointestinal tumors. Methods Among patients treated for gastrointestinal tumors at the First Affiliated Hospital of Wannan Medical College between December 2020 and March 2022, 572 patients were reviewed as the tumor group, and 700 healthy subjects from the physical examination center of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…According to the findings in Figure 3C, hsa_circ_0124554 may be more useful than CA19-9 in the diagnosis of patients with suspected CRC. Studies have reported that the AUC of CEA in the diagnosis of CRC ranged from 0.709 to 0.739, [25][26][27] but our data showed that the AUC of CEA was 0.831, which may be related to the insufficient sample size in our study. In addition to evaluating the performance of each single marker in detection, we also combined 2 or 3 tumor markers to find the optimal diagnostic combination.…”
Section: Discussioncontrasting
confidence: 67%
“…According to the findings in Figure 3C, hsa_circ_0124554 may be more useful than CA19-9 in the diagnosis of patients with suspected CRC. Studies have reported that the AUC of CEA in the diagnosis of CRC ranged from 0.709 to 0.739, [25][26][27] but our data showed that the AUC of CEA was 0.831, which may be related to the insufficient sample size in our study. In addition to evaluating the performance of each single marker in detection, we also combined 2 or 3 tumor markers to find the optimal diagnostic combination.…”
Section: Discussioncontrasting
confidence: 67%
“…Its level is related to tumor size, staging, and metastasis, and it is a relatively new tumor marker in the detection of gastrointestinal and ovarian cancer. 24 Wu noted that pancreatic cancer patients showed a significant upward trend in serum CEA, CA19-9, and CA72-4 levels, with high predictive value for the prognosis of pancreatic cancer patients. 25 Hu suggested that chemotherapy effectively reduced the levels of serum CEA, CA19-9, and CA72-4 in patients with pancreatic cancer and improved their clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of malignant changes in GC is metastasis [20]. Traditional markers CEA, CA199 and CA724 are currently used as the main serum markers for GC screening in the clinic, however, due to the limitation of speci city and sensitivity in the early stage of GC, most of these serum markers are relatively limited in the detection of GC [21,22], so it is crucial to nd new serum markers for the clinic that can dynamically monitor the development of GC. For a long time, scientists have been trying to nd suitable markers for GC, and many potential molecules have been identi ed.…”
Section: Discussionmentioning
confidence: 99%